Essays on culture and disease - Mohanty, Aatishya (Nanyang Technological University, 2023)
This thesis contains three independent essays that explore the association between culture and disease. The persistence of cultural complexities, especially the individualism-collectivism divergence across regions plays a key role in influencing the beliefs, behavior and societal norms of modern times and has been found to be an important determinant of long-run economic development. The essays in this thesis contribute to this line of inquiry by empirically examining questions pertaining to the individualism-collectivism dichotomy and its subsequent link to health outcomes.